Increased Prevalence of Immunoglobulin A Deficiency in Patients with the Chromosome 22q11.2 Deletion Syndrome (DiGeorge Syndrome/Velocardiofacial Syndrome) - Smith, Christopher A. (American Society for Microbiology, 1998)
We wished to determine the prevalence of immunoglobulin A (IgA) deficiency in patients with the chromosome 22q11.2 deletion syndrome. A total of 32 patients with the chromosome 22q11.2 deletion were examined for IgA deficiency. We report a 13% (n = 4) prevalence of IgA deficiency in patients with this syndrome. The odds ratio of IgA deficiency in this population is 14.20 (P < 0.0001). This confirms the occurrence of significant humoral deficits in this predominantly cellular immunodeficiency.